ChemInform Abstract: Direct Access to 2‐Aminopyrazolo[1, 5‐a]pyridines via N‐Amination/Cyclization Reactions of 2‐Pyridineacetonitriles. Issue 15 (April 2015) - Nishigaya, Yosuke; Umei, Kentaro; Yamamoto, Eri; Kohno, Yasushi; Seto, Shigeki
Abstract: The two‐step one‐pot procedure delivers substituted 2‐aminopyrazolo[1, 5‐a]pyridines as scaffolds in medicinal chemistry.